Cognitive behavioural therapy for worry in young individuals with at-risk mental states: a preliminary investigation. (2019) - Pozza, Andrea; Domenichetti, Sandro; Dèttore, Davide
Abstract: Cognitive behavioural therapy (CBT) is a first-line strategy in reducing or delaying risk of transition to psychosis among young individuals with at-risk mental states (ARMS). However, there is little knowledge about its effects on other outcomes associated with ARMS. No study on CBT for ARMS has assessed worry, an important process associated with this condition. The present study investigated changes in worry at immediate post-treatment and 14-month follow-up after CBT for young individuals with ARMS seeking psychiatric care in mental health services. Thirty-seven young individuals (mean age = 26 years, SD = 6.07; 22.20% female) seeking psychiatric care in mental health services and classified as reporting ARMS through the Comprehensive Assessment of At-Risk Mental States were included. The Positive And Negative Syndrome Scales (PANSS) and Penn State Worry Questionnaire (PSWQ) were administered at baseline, post-treatment, and follow-up. CBT consisted of 30 weekly individual 1-hour sessions based on a validated CBT for ARMS manual enriched with components targeting worry [psychoeducation, problem-solving, (meta)cognitive restructuring, behavioural experiments]. Seven participants (18.91%) at follow-up had cumulatively made transition to psychosis. Repeated measures ANOVA with post-hoc pairwise comparisons showed significant changes in PSWQ scores from baseline to post-treatment and from baseline to follow-up; PSWQ scores remained stable from post-treatment to follow-up. This is the first study investigating changes in worry after CBT for ARMS, which appears to be a promising strategy also for this outcome. Future research with a larger sample size and control group may determine whether changes in worry are also associated with reduced transition risk. Key learning aims: (1) To understand CBT evidence and procedures for young individuals with ARMS. (2) To reflect on the current limitations in the literature on CBT for ARMS. (3) To understand the importance and clinical implications of assessing worry in ARMS. (4) To focus on changes in worry as an outcome after CBT for ARMS. (5) To reflect on future research directions on the role of worry in CBT for ARMS.